Al-Muqrinat cave in the countryside of Cyrene: revisiting the prehistoric engravings. (November 2022) - El Mayer, Adel Othman
Abstract: Al-Muqrinat cave was first visited by the Italian researcher Umberto Paradisi in June 1964, after he was told by the locals of its location. Paradisi in turn conducted the first field study in the region. Archaeologist Charles McBurney made some observations on the study particularly with respect to the history of the engravings and the site was referred to as being the first discovery of rock art in the Green Mountain. No further field studies were carried out until 2001, when Libyan student Saad Buhajar investigated the site as part of his master's research. This article is the result of intermittent visits to the cave over a period of 27 years and provides the accurate descriptions of findings including new discoveries.